Enzyme immunoassays in diagnostic medicine: Theory and practice - Voller, A. (1976)
Serological methods are playing an increasingly important role in the diagnosis and epidemiological assessment of diseases. Simple, inexpensive methods for large-scale application are urgently needed. The enzyme immunoassay methods developed recently and reviewed here hold great promise for application in a wide variety of conditions. Under laboratory conditions they can be as sensitive as radio-immunoassay, but they can also be adapted as simple field screening procedures. These methods are based on the use of antibodies or antigens that are linked to an insoluble carrier surface. This is then used to “capture” the relevant antigen or antibody in the test solution and the complex is detected by means of an enzyme-labelled antibody or antigen. The degradation of the enzyme substrate, measured photometrically, is proportional to the concentration of the unknown “antibody” or “antigen” in the test solution. The application of these techniques to endocrinology, immunopathology, haematology, microbiology, and parasitology is reviewed.